The lost magician - Torday, Piers, 1974- (London : Quercus Children's Books, 2018)
1945. They have survived the Blitz, but when Simon, Patricia, Evelyn and Larry step through a mysterious library door, it is the beginning of their most dangerous adventure yet. They discover the magical world of Folio, where an enchanted kingdom of fairy knights, bears and tree gods is under threat from a sinister robot army. The many stories of the Library are locked in eternal war, and the children's only hope is to find their creator - a magician who has been lost for centuries. What they find will change not just their own lives, but the fate of the world, for ever ...
Keywords: Fantastic fiction; Children's stories